Zwei Fenster mit verschiedener Sicht - Scharlau, Ingrid; Karsten, Andrea; Nettingsmeier, Pia; Golombek, Christiane; Schäfer, Stefanie (Akademisches Schreiben. Halbband 1: Vom Qualitätspakt Lehre geförderte Schreibzentren und Schreibwerkstätten)

Vandalism Detection in Wikidata - Heindorf, Stefan; Potthast, Matthias; Stein, Benno; Engels, Gregor (Proceedings of the 25th International Conference on Information and Knowledge Management (CIKM 2016))
Wikidata is the new, large-scale knowledge base of the Wikimedia Foundation. Its knowledge is increasingly used within Wikipedia itself and various other kinds of information systems, imposing high demands on its integrity.Wikidata can be edited by anyone and, unfortunately, it frequently gets vandalized, exposing all information systems using it to the risk of spreading vandalized and falsified information. In this paper, we present a new machine learning-based approach to detect vandalism in Wikidata.We propose a set of 47 features that exploit both content and context information, and we report on 4 classifiers of increasing effectiveness tailored to this learning task. Our approach is evaluated on the recently published Wikidata Vandalism Corpus WDVC-2015 and it achieves an area under curve value of the receiver operating characteristic, ROC-AUC, of 0.991. It significantly outperforms the state of the art represented by the rule-based Wikidata Abuse Filter (0.865 ROC-AUC) and a prototypical vandalism detector recently introduced by Wikimedia within the Objective Revision Evaluation Service (0.859 ROC-AUC).

Digitale Welt und Gesundheit. eHealth und mHealth – Chancen und Risiken der Digitalisierung im Gesundheitsbereich - Schlegel-Matthies, Kirsten; Gigerenzer, Gerd; Wagner, Gert G.

Human-Machine Autonomies - Weber, Jutta; Suchman, Lucy (Autonomous Weapon Systems. Law, Ethics, Policy)

Keep Adding. Kill Lists, Drone Warfare and the Politics of Databases - Weber, Jutta (Environment and Planning D. Society and Space. Special Issue on ‚The Politics of the List: Law, Security, Technology‘ (Hg.: Marieke de Goede/Anna Leander/Gavin Sullivan))

Ethical Regulations on Robotics in Europe - Weber, Jutta; Nagenborg, Michael; Capurro, Rafael; Pingel, Christoph (Machine Ethics and Robot Ethics)

Plants as Digital Things - Alpsancar, Suzana (Tecnoscienza. Italian Journal of Science & Technology Studies)
Seeds have traditionally been collected according to their reproductive cycles, i.e. the time when they lose their potential of becoming a real plant. Therefore, the locations of botanic gardens or seed banks imply the vicinity of agricultural land. This article exemplifies the transformation of plant collections into gene and data banks by investigating the Svalbard Global Seed Vault (SGSV) in Norway and the German Genebank for Fruit Crops (DGO). It shows that international efforts to safeguard biodiversity by intertwining them with bioinformatics infrastructure transform seeds and other plant genetic material into digitalized objects. The almost virtual genetic material, now stored without the neighborhood of acres or gardens, is, at the same time, seen as “options” for new high-tech plants, which might be transplanted to a future territory. Consequently, plant varieties are circulating around the globe in form of genetic material and data. The article shows that the digitalization induces a specific distinction between the material and the digital flows of plants.

A Linear Time Algorithm for Quantum 2-SAT - de Beaudrap, Niel; Gharibian, Sevag (Proceedings of the 31st Conference on Computational Complexity (CCC 2016))
The Boolean constraint satisfaction problem 3-SAT is arguably the canonical NP-complete problem. In contrast, 2-SAT can not only be decided in polynomial time, but in fact in deterministic linear time. In 2006, Bravyi proposed a physically motivated generalization of k-SAT to the quantum setting, defining the problem "quantum k-SAT". He showed that quantum 2-SAT is also solvable in polynomial time on a classical computer, in particular in deterministic time O(n^4), assuming unit-cost arithmetic over a field extension of the rational numbers, where n is number of variables. In this paper, we present an algorithm for quantum 2-SAT which runs in linear time, i.e. deterministic time O(n+m) for n and m the number of variables and clauses, respectively. Our approach exploits the transfer matrix techniques of Laumann et al. [QIC, 2010] used in the study of phase transitions for random quantum 2-SAT, and bears similarities with both the linear time 2-SAT algorithms of Even, Itai, and Shamir (based on backtracking) [SICOMP, 1976] and Aspvall, Plass, and Tarjan (based on strongly connected components) [IPL, 1979].
Keywords: quantum 2-SAT; transfer matrix; strongly connected components; limited backtracking; local Hamiltonian

Lavoro digitale e imperialismo - Fuchs, Christian (Sinistrainrete)

Racism, Nationalism and Right-Wing Extremism Online: The Austrian Presidential Election 2016 on Facebook - Fuchs, Christian (Momentum Quarterly – Zeitschrift für sozialen Fortschritt (Journal for Societal Progress))

Critical Theory of Communication as Critical Sociology of Critique in the Age of Digital Capitalism: A Response to Jan Løhmann Stephensen's Rview Essay on Culture and Economy in the Age of Social Media - Fuchs, Christian (Conjunctions: Transdisciplinary Journal of Cultural Participation)

Henryk Grossmann 2.0: A Critique of Paul Mason’s Book “PostCapitalism: A Guide to Our Future“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

When Will Greece Get its Money Back from Germany? Reflections on Yanis Varoufakis’ New Book - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Capitalism Today: The Austrian Presidential Election and the State of the Right and the Left in Europe - Fuchs, Christian (LSE Euro Crisis in the Press-blog)

The Multiple Aspects of Politics and Sustainability in Community Networks. EU Horizon 2020 Project netCommons, Deliverable 2.1 (Version 1, June 2016) - Fuchs, Christian

Reiseimpressionen zwischen Differenz und Transkulturalität in Wolfgang Büschers "Ein Frühling in Jerusalem" - Müller, Inez (Cadernos de Literatura Comparada)

Herbert Marcuse and Social Media - Fuchs, Christian (Radical Philosophy Review)

What The US Presidential Election Result Tells Us About the Failures Of Big Data Analytics And Neoliberalism As Big Data Capitalism - Fuchs, Christian (The Huffington Post)

User-Generated Ideology on Social Media: A New Study Shows How Users Oppose and Support Jeremy Corbyn on Twitter - Fuchs, Christian (The Huffington Post)

Legal Struggles in the Age of Uber-Capitalism: Are Uber-Drivers Workers or Self-Employed? - Fuchs, Christian (The Huffington Post)

The Facebook/Admiral Scandal Shows The Limits And Dangers Of Big Data Capitalism - Fuchs, Christian (The Huffington Post)

Bosses’ right to snoop on staff emails is an invasion of privacy and ignores the way we work - Fuchs, Christian (New Statesman Online)

Bosses’ right to snoop on staff emails is an invasion of privacy and ignores the way we work - Fuchs, Christian (The Conversation)

Expanding tweets from 140 characters to 10,000? Not nearly radical enough - Fuchs, Christian (The Conversation)

Social Media Research: A Guide to Ethics - Fuchs, Christian; Townsend, Leanne; Wallace, Claire; Jessop, Curtis; Harte, Dave; Perez Vallejos, Elvira; Lepps, Hayley; Holden, Jennifer; Orton Johnston, Kate; Sloan, Luke; Smith, Michael; McGregor, Samantha; et al.

Strategies moving forward: Social movements and progressive governments: A round table discussion - Fuchs, Christian; Smith, R.C.; Gunn, Richard; Asher, Gordon; Cole, Penny (Heathwood Journal of Critical Theory)

Neoliberalism in Britain: From Thatcherism to Cameronism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Selective surface modification in bimodal mesoporous CMK-5 carbon - Weinberger, Christian; Cao, X.; Tiemann, Michael (Journal of Materials Chemistry A)
Ordered, bimodal mesoporous CMK-5 carbon is prepared by using mesoporous SBA-15 silica as a structural mold. The carbon material is chemically modified by oxidative treatment with acidic persulfate solution. This leads to the creation of oxygen-containing functionalities at the pore walls of the carbon (up to 13 wt% oxygen), as confirmed by IR spectroscopy. The oxidative treatment is carried out before removal of the silica mold which ensures that only one of the two distinct modes of mesopores (namely, the intra-tubular pores) is affected; the other mode (inter-tubular pores) is protected from oxidation by the presence of the silica mold. This is proven by water vapor physisorption analysis. The oxidatively treated (intra-tubular) pores are significantly more polar and, hence, better wettable than the untreated (inter-tubular) pores.

Tolerance Analysis of Adhesive Bonds in Crash Simulation - Schwarzkopf, G.; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson; Matzenmiller, A. (Procedia CIRP)
The influences of geometrical parameters like adhesive layer thickness and gap-filling on the mechanical properties of adhesively bonded joints are investigated by means of experimental studies with controlled parameter variations. In addition, corresponding simulation models are used to analyse these effects. As a result, the behaviour of joints under variation of manufacturing parameters can be reproduced with high accuracy. Furthermore, the validated simulation models are used to perform sensitivity analysis on a component-like specimen. Based on these studies, tolerance ranges can be specified and robust design optimisation can be carried out.
Keywords: General Medicine

„Geruchswahrnehmung aus der Luft ist meines Wissens nach gestattet.“ Daten, Drohnen, Drogenfahndung am Beispiel des Cannachoppers - Rolf, Carolin; Shnayien, Mary (onlinejournal kultur & geschlecht)
Big Data als Technik und Analyseinstrument gesellschaftlicher und ökonomischer Zusammenhänge dringt in weite Bereiche des Alltags vor, obgleich die Folgen dieser neuen Technik noch nicht absehbar sind. In diesem Zusammenhang gewinnen auch Drohnen als unterstützender Teil polizeilicher Ermittlungsverfahren immer mehr an Bedeutung. Eine dieser Drohnen ist der Cannachopper, der, begünstigt durch eine Gesetzeslücke, im April 2009 von der niederländischen Polizei eingesetzt wurde, um illegale Hanfplantagen ausfindig zu machen. Der Artikel kann als Ergänzung zum im Anhang befindlichen Skript des gleichnamigen Radiofeatures gelesen werden und situiert den Cannachopper in einem Gefüge aus Begehren und Wünschen nach Sicherheit, effizienter und kostengünstiger Polizeiarbeit und der Dystopie von totaler Überwachung.

Entanglement classification with matrix product states - Sanz, M.; Egusquiza, I.L.; Candia, R. Di; Saberi, H.; Lamata, L.; Solano, E. (Scientific Reports)
We propose an entanglement classification for symmetric quantum states based on their diagonal matrix-product-state (MPS) representation. The proposed classification, which preserves the stochastic local operation assisted with classical communication (SLOCC) criterion, relates entanglement families to the interaction length of Hamiltonians. In this manner, we establish a connection between entanglement classification and condensed matter models from a quantum information perspective. Moreover, we introduce a scalable nesting property for the proposed entanglement classification, in which the families for N parties carry over to the N + 1 case. Finally, using techniques from algebraic geometry, we prove that the minimal nontrivial interaction length n for any symmetric state is bounded by .

Precession and nutation dynamics of nonlinearly coupled non-coaxial three-dimensional matter wave vortices - Driben, R.; Konotop, V. V.; Meier, Torsten (Scientific Reports)
Nonlinearity is the driving force for numerous important effects in nature typically showing transitions between different regimes, regular, chaotic or catastrophic behavior. Localized nonlinear modes have been the focus of intense research in areas such as fluid and gas dynamics, photonics, atomic and solid state physics etc. Due to the richness of the behavior of nonlinear systems and due to the severe numerical demands of accurate three-dimensional (3D) numerical simulations presently only little knowledge is available on the dynamics of complex nonlinear modes in 3D. Here, we investigate the dynamics of 3D non-coaxial matter wave vortices that are trapped in a parabolic potential and interact via a repulsive nonlinearity. Our numerical simulations demonstrate the existence of an unexpected and fascinating nonlinear regime that starts immediately when the nonlinearity is switched-on and is characterized by a smooth dynamics representing torque-free precession with nutations. The reported motion is proven to be robust regarding various effects such as the number of particles, dissipation and trap deformations and thus should be observable in suitably designed experiments. Since our theoretical approach, i.e., coupled nonlinear Schrödinger equations, is quite generic, we expect that the obtained novel dynamical behavior should also exist in other nonlinear systems.

Rezension von: Jutta Berger / Christian Schmidtmann (Hgg.): Referendariat Geschichte. Kompaktwissen für Berufseinstieg und Examensvorbereitung, Berlin: Cornelsen 2014 - Hartung, Olaf (sehepunkte)

Investigations into Bluetooth Low Energy Localization Precision Limits - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (24th European Signal Processing Conference (EUSIPCO 2016))
In this paper we study the influence of directional radio patterns of Bluetooth low energy (BLE) beacons on smartphone localization accuracy and beacon network planning. A two-dimensional model of the power emission characteristic is derived from measurements of the radiation pattern of BLE beacons carried out in an RF chamber. The Cramer-Rao lower bound (CRLB) for position estimation is then derived for this directional power emission model. With this lower bound on the RMS positioning error the coverage of different beacon network configurations can be evaluated. For near-optimal network planing an evolutionary optimization algorithm for finding the best beacon placement is presented.

Abschlussbericht zum 2. Summer Institute der Gesellschaft für Musikwirtschafts- und Musikkulturforschung “Developments for Musicpreneurs: 14. – 20. September 2016, Porto, Portugal“. - Jacke, Christoph; Gödde, Jonas; Nösner, Dominik

Eine gute Gelegenheit für Integration. Der Burgundische Reichskreis auf dem Reichstag zu Speyer 1570 - Huybrechts, Yves (Speyer als Hauptstadt des Reiches – Politik und Justiz zwischen Reich und Territorium im 16. und 17. Jahrhundert)

Ausweitung der Machbarkeitszone. Ästhetisch-technische Modernitätskonzepte von Film und Partitur in Arnold Fancks und Paul Hindemiths »In Sturm und Eis« (1921) - Münzmay, Andreas (Spiel (mit) der Maschine: Musikalische Medienpraxis in der Frühzeit von Phonografie, Selbstspielklavier, Film und Radio)
In der Frühzeit von Phonographie, Reproduktionsklavier, Film und Radio wurden die damals neuen Medien nicht nur untereinander verknüpft, sondern auch mit der traditionellen musikalischen Praxis des Instrumentalspiels kombiniert. Der Band beleuchtet diese heute weitgehend vergessenen, vielfältig ausdifferenzierten Felder musikalischer Medienpraxis. Neben der Frage nach der musik- und medienhistoriographischen Relevanz solch ephemerer musikalischer Mediengemische widmen sich die Beiträge den komplexen Verflechtungen zwischen den neu entstandenen Reproduktions- und Übertragungsmedien, dem naturwissenschaftlichen und ästhetischen Denken der Zeit sowie den ökonomischen Entwicklungen. Darüber hinaus werden medienästhetische Strategien beleuchtet, mit denen die neuen technischen Geräte künstlerisch umgedeutet wurden.
Keywords: Filmmusik; Arnold Fanck; Paul Hindemith

Nicolaus Taurellus - Blank, Andreas (Stanford Encyclopedia of Philosophy)

Rekonstruktion des Governance-Regimes des Transfers von Bildung für nachhaltige Entwicklung - Heinrich, Martin; Bormann, Inka; Hamborg, Steffen; Lambrecht, Maike; Nikel, Jutta; Haker, Christoph; Brüsemeister, Thomas (Governance-Regime des Transfers von Bildung für nachhaltige Entwicklung: Qualitative Rekonstruktionen)
Gegenstand des Teils IV ist die Triangulation der in den vorangegangenen Kapiteln präsentierten Untersuchungen mit dem Ziel, auf der Basis ausgewählter Dokumente und Interviews mit staatlichen und zivilgesellschaftlichen Akteuren aus ausgewählten Bundesländern und Kommunen ein Governance-Regime des BNE-Transfers zu rekonstruieren, wie es sich im Rahmen der UN-Dekade darstellt. Zu diesem Zweck erfolgt zum einen die Gegenüberstellung und Diskussion der methodologischen Perspektiven, auf die im Rahmen der einzelnen Untersuchungen zurückgegriffen wurde, um Schnittmengen und Unterschiede der jeweiligen Perspektiven auf den Gegenstandsbereich des BNE-Transfers (und darin jeweils spezifisch konstruierter Gegenstände) und die Möglichkeiten ihrer Zusammenführung abzuwägen. Zum anderen wird auf der Basis der jeweiligen Ergebnisse und unter dem Vorbehalt der Unvereinbarkeit einiger theoretischer und methodologischer Positionen, auf denen diese Ergebnisse basieren, das Bild eines Governance-Regimes entworfen, wie es sich in der Gesamtschau der vorgestellten Untersuchungen und ihrer wechselseitigen Bezüge auf der Ebene der hervorgebrachten Ergebnisse abzeichnet.

Inhaltsanalytisch-prozessuale Mechanismenanalyse - Haker, Christoph; Nikel, Jutta (Governance-Regime des Transfers von Bildung für nachhaltige Entwicklung: Qualitative Rekonstruktionen)
Die inhaltsanalytisch-prozessuale Mechanismenanalyse ist ein Label, welches wir unserem methodischen Vorgehen im Teilprojekt „Handlungskoordination zwischen staatlichen und zivilgesellschaftlichen Akteuren im BNE-Transfer in ausgewählten Bundesländern“ geben. Wir haben diese Methode sukzessive, während der unterschiedlichen Arbeitsphasen in unserem Projekt, entwickelt. Sie stellt also keine etablierte oder geschlossene Methodenschule dar, sondern expliziert unser konkretes Vorgehen auf einem stark generalisierten Niveau.

Governance von Transferprozessen im Mehrebenensystem - Bormann, Inka; Heinrich, Martin; Hamborg, Steffen; Lambrecht, Maike; Nikel, Jutta; Haker, Christoph; Brüsemeister, Thomas (Governance-Regime des Transfers von Bildung für nachhaltige Entwicklung)

Handlungskoordination zwischen staatlichen und zivilgesellschaftlichen Akteuren im BNE-Transfer - Nikel, Jutta; Haker, Christoph (Governance-Regime des Transfers von Bildung für nachhaltige Entwicklung)

Entscheidend ist wer mitbestimmt – Potenziale für Inklusion im Sportverein - Meier, Heiko; Adolph-Börs, Cindy; Seitz, Simone (Zeitschrift für Inklusion)
Inklusion ist als Schlagwort seit der Ratifizierung der UN-Behindertenrechtskonvention (United Nations, 2006) im Jahr 2009 in aller Munde. Die Hauptaufmerksamkeit in der Rezeption der UN-Behindertenrechtskonvention liegt im deutschsprachigen Raum auf dem Erziehungs- und Bildungssystem. Weniger Beachtung finden in den Diskussionen demgegenüber die weiteren Lebensbereiche, die in der UN-BRK thematisiert werden, etwa die Partizipation am und im Sport. So sind Sportvereine aktuell gefordert, wirksame Strategien zur Realisierung von Inklusion zu entwickeln. Die Frage, wie diese Strategien aussehen können, ist derzeit noch ein umfassendes Forschungsdesiderat. Diesem haben wir uns im Auftrag des Ministeriums für Familie, Kinder, Jugend, Kultur und Sport NRW im Rahmen der wissenschaftlichen Begleitung eines Vereinsentwicklungsprojektes angenommen, welches gemeinsam vom Landessportbund NRW und dem Behinderten- und Rehabilitationssportverband NRW von 2013 bis 2016 durchgeführt wurde. Die Untersuchung verbindet qualitative und quantitative Forschungsinstrumente und nimmt unterschiedliche Akteursebenen in den Blick. Als bedeutsam erweisen sich in der Untersuchung vor allem die Ambivalenzen, die sich aus den tradierten Vereinskulturen ergeben. Diese zeigen sich im Feld der sportlichen Praxis und auf struktureller Ebene, aber auch im Feld der Mitbestimmung im Verein. Im Beitrag werden nach einer theoretischen Einordnung ausgewählte Forschungsergebnisse zu den Möglichkeiten eines diskriminierungsfreien Zugangs zu den demokratischen Gremien von Sportvereinen vorgestellt und Perspektiven für die inklusive Vereinsentwicklung diskutiert.
Keywords: Partizipation; Mitbestimmung; Demokratie; Inklusion; Sportverein

Scherzo g-Moll und Harmonies funèbres WoO II/1 und 4 - Fütterer, Daniel; Gawlok, Judith; Lamprecht, Annelie; Ried, Dennis (Mitteilungen der IMRG)

Rezension zu: Kline, Ronald R.: The Cybernetics Moment. Or Why We Call Our Age the Information Age. Baltimore 2015 - Schmitt, Martin (H-Soz-Kult)

Art. ‚Schulbücher, aktuelle, katholisch, Grundschule / Förderschule‘ - Reis, Oliver (Das Wissenschaftlich-Religionspädagogische Lexikon (WiReLex), Februar 2016)

Art. ‚Schulbücher aktuelle, katholisch, Mittelstufe/Oberstufe‘ - Reis, Oliver (WiReLex, Februar 2016)

Live and (digital) life. Some notes on interaction with music - Flath, Beate

Automating Geospatial RDF Dataset Integration and Enrichment - Sherif, Mohamed
Over the last years, the Linked Open Data (LOD) has evolved from a mere 12 to more than 10, 000 knowledge bases. These knowledge bases come from diverse domains including (but not limited to) publications, life sciences, social networking, government, media, linguistics. Moreover, the LOD cloud also contains a large number of crossdomain knowledge bases such as DBpedia and Yago2. These knowledge bases are commonly managed in a decentralized fashion and contain partly overlapping information. This architectural choice has led to knowledge pertaining to the same domain being published by independent entities in the LOD cloud. For example, information on drugs can be found in Diseasome as well as DBpedia and Drugbank. Furthermore, certain knowledge bases such as DBLP have been published by several bodies, which in turn has lead to duplicated content in the LOD. In addition, large amounts of geo-spatial information have been made available with the growth of heterogeneous Web of Data. The concurrent publication of knowledge bases containing related information promises to become a phenomenon of increasing importance with the growth of the number of independent data providers. Enabling the joint use of the knowledge bases published by these providers for tasks such as federated queries, cross-ontology question answering and data integration is most commonly tackled by creating links between the resources described within these knowledge bases. Within this thesis, we spur the transition from isolated knowledge bases to enriched Linked Data sets where information can be easily integrated and processed. To achieve this goal, we provide concepts, approaches and use cases that facilitate the integration and enrichment of information with other data types that are already present on the Linked Data Web with a focus on geo-spatial data. The first challenge that motivates our work is the lack of measures that use the geographic data for linking geo-spatial knowledge bases. This is partly due to the geo-spatial resources being described by the means of vector geometry. In particular, discrepancies in granularity and error measurements across knowledge bases render the selection of appropriate distance measures for geo-spatial resources difficult. We address this challenge by evaluating existing literature for pointset measures that can be used to measure the similarity of vector geometries. Then, we present and evaluate the ten measures that we derived from the literature on samples of three real knowledge bases. The second challenge we address in this thesis is the lack of automatic Link Discovery (LD) approaches capable of dealing with geospatial knowledge bases with missing and erroneous data. To this end,we present Colibri, an unsupervised approach that allows discovering links between knowledge bases while improving the quality of the instance data in these knowledge bases. A Colibri iteration begins by generating links between knowledge bases. Then, the approach makes use of these links to detect resources with probably erroneous or missing information. This erroneous or missing infor- mation detected by the approach is finally corrected or added. The third challenge we address is the lack of scalable LD approaches for tackling big geo-spatial knowledge bases. Thus, we present Deterministic Particle-Swarm Optimization (DPSO), a novel load balancing technique for LD on parallel hardware based on particle-swarm optimization. We combine this approach with the Orchid algorithm for geo-spatial linking and evaluate it on real and artificial data sets. The lack of approaches for automatic updating of links of an evolving knowledge base is our fourth challenge. This challenge is addressed in this thesis by the Wombat algorithm. Wombat is a novel approach for the discovery of links between knowledge bases that relies exclusively on positive examples. Wombat is based on generalisation via an upward refinement operator to traverse the space of Link Specifications (LS). We study the theoretical characteristics of Wombat and evaluate it on different benchmark data sets. The last challenge addressed herein is the lack of automatic approaches for geo-spatial knowledge base enrichment. Thus, we propose Deer, a supervised learning approach based on a refinement operator for enriching Resource Description Framework (RDF) data sets. We show how we can use exemplary descriptions of enriched resources to generate accurate enrichment pipelines. We evaluate our approach against manually defined enrichment pipelines and show that our approach can learn accurate pipelines even when provided with a small number of training examples. Each of the proposed approaches is implemented and evaluated against state-of-the-art approaches on real and/or artificial data sets. Moreover, all approaches are peer-reviewed and published in a con- ference or a journal paper. Throughout this thesis, we detail the ideas, implementation and the evaluation of each of the approaches. Moreover, we discuss each approach and present lessons learned. Finally, we conclude this thesis by presenting a set of possible future extensions and use cases for each of the proposed approaches.
Keywords: 2016 group_aksw sys:relevantFor:geoknow sys:relevantFor:infai sys:relevantFor:bis ngonga simba dice sherif group_aksw geoknow deer lehmann MOLE

Anonymous and Publicly Linkable Reputation Systems - Blömer, Johannes; Juhnke, Jakob; Kolb, Christina (Proceedings of the 18th International Conference on Financial Cryptography and Data Security (FC))
Reputation systems are used to compute and publish reputation scores for services or products. We consider reputation systems where users are allowed to rate products that they purchased previously. To obtain trustworthy reputations, they are allowed to rate these products only once. As long as users rate products once, they stay anonymous. Everybody is able to detect users deviating from the rate-products-only-once policy and the anonymity of such dishonest users can be revoked by a system manager. In this paper we present formal models for such reputation systems and their security. Based on group signatures presented by Boneh, Boyen, and Shacham we design an efficient reputation system that meets all our requirements.

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

Tightly-Secure Signatures from Chameleon Hash Functions - Blazy, Olivier; Kakvi, Saqib; Kiltz, Eike; Pan, Jiaxin (Lecture Notes in Computer Science)

Efficient Verifier-Local Revocation for Anonymous Credentials - Bobolz, Jan

Does technological change drive inclusive industrialization? - A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

Erfahrungsberichte aus zweiter Hand: Erkenntnisse über die Autorschaft von Arztbewertungen in Online-Portalen - Geierhos, Michaela; Bäumer, Frederik Simon (DHd 2015: Book of Abstracts)

Der zufriedene Patient 2.0: Analyse anonymer Arztbewertungen zur Generierung eines Patientenstimmungsbildes - Geierhos, Michaela; Schulze, Sabine (ForschungsForum Paderborn)
Der Erfahrungsaustausch zwischen Patienten findet heutzutage zunehmend im Internet statt. Bewertungsportale wie jameda, DocInsider oder imedo.de bieten Patienten und deren Angehörigen die Möglichkeit, anonym Beschwerden zu äußern oder Weiterempfehlungen auszusprechen. Gleichzeitig ermöglichen diese hunderttausend Individualerfahrungen die Erhebung der Patientenzufriedenheit sowie die Überprüfung bestehender Gerüchte, wie z. B. dass Privatpatienten schneller einen Arzttermin bekommen und weniger Zeit im Wartezimmer verbringen. Die Analyse anonymer Online-Arztbewertungen kann nur dann erfolgreich sein, wenn bei der Interpretation der Patientenerfahrungsberichte berücksichtigt wird, dass behandlungsqualitätsunabhängige Faktoren Auswirkungen auf die subjektive Bewertung und das Beschwerdeverhalten haben. Ein neuer Ansatz ist daher, bedeutende Indikatoren für die Patientenzufriedenheit im Web 2.0 zur Generierung eines detaillierten Erfahrungs- und Patientenstimmungsbildes unter Berücksichtigung demographischer und regionaler Einflüsse zu ermitteln.

Voronoi Cells of Lattices with Respect to Arbitrary Norms - Blömer, Johannes; Kohn, Kathlén
Motivated by the deterministic single exponential time algorithm of Micciancio and Voulgaris for solving the shortest and closest vector problem for the Euclidean norm, we study the geometry and complexity of Voronoi cells of lattices with respect to arbitrary norms.On the positive side, we show that for strictly convex and smooth norms the geometry of Voronoi cells of lattices in any dimension is similar to the Euclidean case, i.e., the Voronoi cells are defined by the so-called Voronoi-relevant vectors and the facets of a Voronoi cell are in one-to-one correspondence with these vectors. On the negative side, we show that combinatorially Voronoi cells for arbitrary strictly convex and smooth norms are much more complicated than in the Euclidean case.In particular, we construct a family of three-dimensional lattices whose number of Voronoi-relevant vectors with respect to the l_3-norm is unbounded.Since the algorithm of Micciancio and Voulgaris and its run time analysis crucially dependonthefactthatfortheEuclidean normthenumber of Voronoi-relevant vectors is single exponential in the lattice dimension, this indicates that the techniques of Micciancio and Voulgaris cannot be extended to achieve deterministic single exponential time algorithms for lattice problems with respect to arbitrary l_p-norms.

High-Performance Computing for Scheduling Decision Support: A Parallel Depth-First Search Heuristic - Rauchecker, Gerhard; Schryen, Guido (Australasian Conference on Information Systems)
Many academic disciplines - including information systems, computer science, and operations management - face scheduling problems as important decision making tasks. Since many scheduling problems are NP-hard in the strong sense, there is a need for developing solution heuristics. For scheduling problems with setup times on unrelated parallel machines, there is limited research on solution methods and to the best of our knowledge, parallel computer architectures have not yet been taken advantage of. We address this gap by proposing and implementing a new solution heuristic and by testing different parallelization strategies. In our computational experiments, we show that our heuristic calculates near-optimal solutions even for large instances and that computing time can be reduced substantially by our parallelization approach.
Keywords: scheduling; decision support; heuristic; high performance computing; parallel algorithms

Revenue Management for Cloud Computing Providers: Decision Models for Service Admission Control under Non-probabilistic Uncertainty - Püschel, Tim; Schryen, Guido; Hristova, Diana; Neumann, Dirk (European Journal of Operational Research)
Cloud computing promises the flexible delivery of computing services in a pay-as-you-go manner. It allows customers to easily scale their infrastructure and save on the overall cost of operation. However Cloud service offerings can only thrive if customers are satisfied with service performance. Allow-ing instantaneous access and flexible scaling while maintaining the service levels and offering competitive prices poses a significant challenge to Cloud Computing providers. Furthermore services will remain available in the long run only if this business generates a stable revenue stream. To address these challenges we introduce novel policy-based service admission control mod-els that aim at maximizing the revenue of Cloud providers while taking in-formational uncertainty regarding resource requirements into account. Our evaluation shows that policy-based approaches statistically significantly out-perform first come first serve approaches, which are still state of the art. Furthermore the results give insights in how and to what extent uncertainty has a negative impact on revenue.
Keywords: admission control; informational uncertainty; revenue management; cloud computing

Specification of Complex Structures in Distributed Service Function Chaining Using a YANG Data Model - Dräxler, Sevil; Karl, Holger (CoRR)

Requirements for IT Security Metrics - An Argumentation Theory Based Approach - Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

A Multi-Theoretical Literature Review on Information Security Investments using the Resource-Based View and the Organizational Learning Theory - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (International Conference on Information Systems)
The protection of information technology (IT) has become and is predicted to remain a key economic challenge for organizations. While research on IT security investment is fast growing, it lacks a theoretical basis for structuring research, explaining economic-technological phenomena and guide future research. We address this shortcoming by suggesting a new theoretical model emerging from a multi-theoretical perspective adopt-ing the Resource-Based View and the Organizational Learning Theory. The joint appli-cation of these theories allows to conceptualize in one theoretical model the organiza-tional learning effects that occur when the protection of organizational resources through IT security countermeasures develops over time. We use this model of IT security invest-ments to synthesize findings of a large body of literature and to derive research gaps. We also discuss managerial implications of (closing) these gaps by providing practical ex-amples.
Keywords: Information Security; Investment; Literature review; Resource-based View; Organi-zational Learning Theory; Multi-theoretical Perspective

IT Security Investments Through the Lens of the Resource-Based View: A new Theoretical Model and Literature Review - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

Towards an Economic Approach to Identity and Access Management Systems Using Decision Theory - Weishäupl, Eva; Kunz, Michael; Yasasin, Emrah; Wagner, Gerit; Prester, Julian; Schryen, Guido; Pernul, Günther (2nd International Workshop on Security in highly connected IT Systems (SHCIS?15))
Nowadays, providing employees with failure-free access to various systems, applications and services is a crucial factor for organizations? success as disturbances potentially inhibit smooth workflows and thereby harm productivity. However, it is a challenging task to assign access rights to employees? accounts within a satisfying time frame. In addition, the management of multiple accounts and identities can be very onerous and time consuming for the responsible administrator and therefore expensive for the organization. In order to meet these challenges, firms decide to invest in introducing an Identity and Access Management System (IAMS) that supports the organization by using policies to assign permissions to accounts, groups, and roles. In practice, since various versions of IAMSs exist, it is a challenging task to decide upon introduction of an IAMS. The following study proposes a first attempt of a decision support model for practitioners which considers four alternatives: Introduction of an IAMS with Role-based Access Control RBAC) or without and no introduction of IAMS again with or without RBAC. To underpin the practical applicability of the proposed model, we parametrize and operationalize it based on a real world use case using input from an expert interview.
Keywords: Identity and Access Management; Economic Decision Making; Information Systems; Information Security Investment; Decision Theory

IT-Sicherheit: Ökonomisch Planen und Bewerten - Schryen, Guido; Weishäupl, Eva (Managementkompass)

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

Resource Planning in Disaster Response - Decision Support Models and Methodologies - Schryen, Guido; Rauchecker, Gerhard; Comes, Martina (Business & Information Systems Engineering (BISE))

Writing qualitative IS literature reviews ? Guidelines for synthesis, interpretation and guidance of research - Schryen, Guido (Communications of the AIS)

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

On Optimal Smoothing in Minimum Statistics Based Noise Tracking - Chinaev, Aleksej; Haeb-Umbach, Reinhold (Interspeech 2015)
Noise tracking is an important component of speech enhancement algorithms. Of the many noise trackers proposed, Minimum Statistics (MS) is a particularly popular one due to its simple parameterization and at the same time excellent performance. In this paper we propose to further reduce the number of MS parameters by giving an alternative derivation of an optimal smoothing constant. At the same time the noise tracking performance is improved as is demonstrated by experiments employing speech degraded by various noise types and at different SNR values.
Keywords: speech enhancement; noise tracking; optimal smoothing

Semantic Analysis of Spoken Input using Markov Logic Networks - Despotovic, Vladimir; Walter, Oliver; Haeb-Umbach, Reinhold (INTERSPEECH 2015)
We present a semantic analysis technique for spoken input using Markov Logic Networks (MLNs). MLNs combine graphical models with first-order logic. They areparticularly suitable for providing inference in the presence of inconsistent and incomplete data, which are typical of an automatic speech recognizer's (ASR) output in the presence of degraded speech. The target application is a speech interface to a home automation system to be operated by people with speech impairments, where the ASR output is particularly noisy. In order to cater for dysarthric speech with non-canonical phoneme realizations, acoustic representations of the input speech are learned in an unsupervised fashion. While training data transcripts are not required for the acoustic model training, the MLN training requires supervision, however, at a rather loose and abstract level. Results on two databases, one of them for dysarthric speech, show that MLN-based semantic analysis clearly outperforms baseline approaches employing non-negative matrix factorization, multinomial naive Bayes models, or support vector machines.

DOA-Estimation based on a Complex Watson Kernel Method - Drude, Lukas; Jacob, Florian; Haeb-Umbach, Reinhold (23th European Signal Processing Conference (EUSIPCO 2015))
This contribution presents a Direction of Arrival (DoA) estimation algorithm based on the complex Watson distribution to incorporate both phase and level differences of captured micro- phone array signals. The derived algorithm is reviewed in the context of the Generalized State Coherence Transform (GSCT) on the one hand and a kernel density estimation method on the other hand. A thorough simulative evaluation yields insight into parameter selection and provides details on the performance for both directional and omni-directional microphones. A comparison to the well known Steered Response Power with Phase Transform (SRP-PHAT) algorithm and a state of the art DoA estimator which explicitly accounts for aliasing, shows in particular the advantages of presented algorithm if inter-sensor level differences are indicative of the DoA, as with directional microphones.

Unsupervised adaptation of a denoising autoencoder by Bayesian Feature Enhancement for reverberant asr under mismatch conditions - Heymann, Jahn; Haeb-Umbach, Reinhold; Golik, P.; Schlueter, R. (Acoustics, Speech and Signal Processing (ICASSP), 2015 IEEE International Conference on)
The parametric Bayesian Feature Enhancement (BFE) and a datadriven Denoising Autoencoder (DA) both bring performance gains in severe single-channel speech recognition conditions. The first can be adjusted to different conditions by an appropriate parameter setting, while the latter needs to be trained on conditions similar to the ones expected at decoding time, making it vulnerable to a mismatch between training and test conditions. We use a DNN backend and study reverberant ASR under three types of mismatch conditions: different room reverberation times, different speaker to microphone distances and the difference between artificially reverberated data and the recordings in a reverberant environment. We show that for these mismatch conditions BFE can provide the targets for a DA. This unsupervised adaptation provides a performance gain over the direct use of BFE and even enables to compensate for the mismatch of real and simulated reverberant data.
Keywords: codecs; signal denoising; speech recognition; Bayesian feature enhancement; denoising autoencoder; reverberant ASR; single-channel speech recognition; speaker to microphone distances; unsupervised adaptation; Adaptation models; Noise reduction; Reverberation; Speech; Speech recognition; Training; deep neuronal networks; denoising autoencoder; feature enhancement; robust speech recognition

Absolute Geometry Calibration of Distributed Microphone Arrays in an Audio-Visual Sensor Network - Jacob, Florian; Haeb-Umbach, Reinhold (ArXiv e-prints)
Joint audio-visual speaker tracking requires that the locations of microphones and cameras are known and that they are given in a common coordinate system. Sensor self-localization algorithms, however, are usually separately developed for either the acoustic or the visual modality and return their positions in a modality specific coordinate system, often with an unknown rotation, scaling and translation between the two. In this paper we propose two techniques to determine the positions of acoustic sensors in a common coordinate system, based on audio-visual correlates, i.e., events that are localized by both, microphones and cameras separately. The first approach maps the output of an acoustic self-calibration algorithm by estimating rotation, scale and translation to the visual coordinate system, while the second solves a joint system of equations with acoustic and visual directions of arrival as input. The evaluation of the two strategies reveals that joint calibration outperforms the mapping approach and achieves an overall calibration error of 0.20m even in reverberant environments.

Robust Automatic Speech Recognition - Li, Jinyu; Deng, Li; Haeb-Umbach, Reinhold; Gong, Y.

Typicality and Emotion in the Voice of Children with Autism Spectrum Condition: Evidence Across Three Languages - Marchi, Erik; Schuller, Bjoern; Baron-Cohen, Simon; Golan, Ofer; Boelte, Sven; Arora, Prerna; Haeb-Umbach, Reinhold (INTERSPEECH 2015)
Only a few studies exist on automatic emotion analysis of speech from children with Autism Spectrum Conditions (ASC). Out of these, some preliminary studies have recently focused on comparing the relevance of selected prosodic features against large sets of acoustic, spectral, and cepstral features; however, no study so far provided a comparison of performances across different languages. The present contribution aims to fill this white spot in the literature and provide insight by extensive evaluations carried out on three databases of prompted phrases collected in English, Swedish, and Hebrew, inducing nine emotion categories embedded in short-stories. The datasets contain speech of children with ASC and typically developing children under the same conditions. We evaluate automatic diagnosis and recognition of emotions in atypical childrens voice over the nine categories including binary valence/arousal discrimination.

Source Counting in Speech Mixtures by Nonparametric Bayesian Estimation of an infinite Gaussian Mixture Model - Walter, Oliver; Drude, Lukas; Haeb-Umbach, Reinhold (40th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2015))
In this paper we present a source counting algorithm to determine the number of speakers in a speech mixture. In our proposed method, we model the histogram of estimated directions of arrival with a nonparametric Bayesian infinite Gaussian mixture model. As an alternative to classical model selection criteria and to avoid specifying the maximum number of mixture components in advance, a Dirichlet process prior is employed over the mixture components. This allows to automatically determine the optimal number of mixture components that most probably model the observations. We demonstrate by experiments that this model outperforms a parametric approach using a finite Gaussian mixture model with a Dirichlet distribution prior over the mixture weights.

Autonomous Learning of Representations - Walter, Oliver; Haeb-Umbach, Reinhold; Mokbel, Bassam; Paassen, Benjamin; Hammer, Barbara (KI - Kuenstliche Intelligenz)
Besides the core learning algorithm itself, one major question in machine learning is how to best encode given training data such that the learning technology can efficiently learn based thereon and generalize to novel data. While classical approaches often rely on a hand coded data representation, the topic of autonomous representation or feature learning plays a major role in modern learning architectures. The goal of this contribution is to give an overview about different principles of autonomous feature learning, and to exemplify two principles based on two recent examples: autonomous metric learning for sequences, and autonomous learning of a deep representation for spoken language, respectively.
Keywords: Representation learning; Metric learning; Deep representation; Spoken language

Lexicon Discovery for Language Preservation using Unsupervised Word Segmentation with Pitman-Yor Language Models (FGNT-2015-01) - Walter, Oliver; Haeb-Umbach, Reinhold; Strunk, Jan; P. Himmelmann, Nikolaus
In this paper we show that recently developed algorithms for unsupervised word segmentation can be a valuable tool for the documentation of endangered languages. We applied an unsupervised word segmentation algorithm based on a nested Pitman-Yor language model to two austronesian languages, Wooi and Waima'a. The algorithm was then modified and parameterized to cater the needs of linguists for high precision of lexical discovery: We obtained a lexicon precision of of 69.2% and 67.5% for Wooi and Waima'a, respectively, if single-letter words and words found less than three times were discarded. A comparison with an English word segmentation task showed comparable performance, verifying that the assumptions underlying the Pitman-Yor language model, the universality of Zipf's law and the power of n-gram structures, do also hold for languages as exotic as Wooi and Waima'a.

How to Break XML Encryption -- Automatically - Kupser, Dennis; Mainka, Christian; Schwenk, Jö; Somorovsky, Juraj (9th USENIX Workshop on Offensive Technologies (WOOT 15))

Does technological change drive inclusive industrialization? A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

Was ist Wahrheit? - Ficara, Elena (Fatum Magazin)

Den individuellen Lernprozess der Studierenden im Blick: Anders betreuen in modernen Laborpraktika - Probst, Heike M.; Sacher, Marc; Schaper, Niclas (Mittendrin - Lehre im Dialog)

Neue Wege zur Konzeption eines kompetenzfördernden, studierendenzentrierten Laborpraktikums - Sacher, Marc (Mittendrin - Lehre im Dialog)

Die Internationale Finanzkommission für Griechenland von 1898 oder: Stereotypen leben lange - Schönhärl, Korinna

Ab initio study of strain effects on the quasiparticle bands and effective masses in silicon - Bouhassoune, Mohammed; Schindlmayr, Arno (Advances in Condensed Matter Physics)
Using ab initio computational methods, we study the structural and electronic properties of strained silicon, which has emerged as a promising technology to improve the performance of silicon-based metal-oxide-semiconductor field-effect transistors. In particular, higher electron mobilities are observed in n-doped samples with monoclinic strain along the [110] direction, and experimental evidence relates this to changes in the effective mass as well as the scattering rates. To assess the relative importance of these two factors, we combine density-functional theory in the local-density approximation with the GW approximation for the electronic self-energy and investigate the effect of uniaxial and biaxial strains along the [110] direction on the structural and electronic properties of Si. Longitudinal and transverse components of the electron effective mass as a function of the strain are derived from fits to the quasiparticle band structure and a diagonalization of the full effective-mass tensor. The changes in the effective masses and the energy splitting of the conduction-band valleys for uniaxial and biaxial strains as well as their impact on the electron mobility are analyzed. The self-energy corrections within GW lead to band gaps in excellent agreement with experimental measurements and slightly larger effective masses than in the local-density approximation.

Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Towards Vandalism Detection in Knowledge Bases - Heindorf, Stefan; Potthast, Martin; Stein, Benno; Engels, Gregor (SIGIR)

Rezension von: Widmer-Wolf, Patrik: Praxis der Individualisierung. Wie multiprofessionelle Klassenteams Fördersituationen für Kinder im Schulalltag etablieren - Neumann, Phillip (Erziehungswissenschaftliche Revue (EWR))

From Science and Technology to Feminist Technoscience - Weber, Jutta (Women, Science, and Technology. A Reader in Feminist Science Studies)

From Science and Technology to Feminist Technoscience - Weber, Jutta (Women, Science, and Technology. A Reader in Feminist Science Studies)

Technokultur, Posthumanität und neue Lebensformen - Weber, Jutta (Cultural Studies und Medienanalyse)

Game Changer? On the Epistemology, Ontology, and Politics of Drones. Behemoth – A Journal on Civilisation Volume 8 Issue No. 2 (Behemoth – A Journal on Civilisation)

MESOSCOPIC MODELING OF THE RTM PROCESS FOR HOMOGENIZATION - Mahnken, Rolf; Dammann, Christian

Flachheitsbasierte Methode zum stoßfreien Umschalten von Reglerstrukturen - Osmic, Semir

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (International Colloquium on Automata, Languages, and Programming (ICALP 2015))
The study of ground state energies of local Hamiltonians has played a fundamental role in quantum complexity theory. In this paper, we take a new direction by introducing the physically motivated notion of ``ground state connectivity'' of local Hamiltonians, which captures problems in areas ranging from quantum stabilizer codes to quantum memories. We show that determining how ``connected'' the ground space of a local Hamiltonian is can range from QCMA-complete to PSPACE-complete, as well as NEXP-complete for an appropriately defined ``succinct'' version of the problem. As a result, we obtain a natural QCMA-complete problem, a goal which has generally proven difficult since the conception of QCMA over a decade ago. Our proofs rely on a new technical tool, the Traversal Lemma, which analyzes the Hilbert space a local unitary evolution must traverse under certain conditions. We show that this lemma is essentially tight with respect to the length of the unitary evolution in question.

Quantum Hamiltonian Complexity - Gharibian, Sevag; Huang, Yichen; Landau, Zeph; Woo Shin, Seung (Foundations and Trends® in Theoretical Computer Science)
Constraint satisfaction problems are a central pillar of modern computational complexity theory. This survey provides an introduction to the rapidly growing field of Quantum Hamiltonian Complexity, which includes the study of quantum constraint satisfaction problems. Over the past decade and a half, this field has witnessed fundamental breakthroughs, ranging from the establishment of a “Quantum Cook-Levin Theorem” to deep insights into the structure of 1D low-temperature quantum systems via so-called area laws. Our aim here is to provide a computer science-oriented introduction to the subject in order to help bridge the language barrier between computer scientists and physicists in the field. As such, we include the following in this survey: (1) The motivations and history of the field, (2) a glossary of condensed matter physics terms explained in computer-science friendly language, (3) overviews of central ideas from condensed matter physics, such as indistinguishable particles, mean field theory, tensor networks, and area laws, and (4) brief expositions of selected computer science-based results in the area. For example, as part of the latter, we provide a novel information theoretic presentation of Bravyi’s polynomial time algorithm for Quantum 2-SAT.